Effectiveness of binahong leaves extract, soursop leaves extract and combination of binahong leaves and soursop leaves extract on hemostasis in cuts of mice - Hasmawati Hasan; Bismi M. Haris (DiscoverSys Inc., 2017)
Objective: Tooth extraction is a process of removing a tooth from the alveolar process which will always cause bleeding. Bleeding is usually occurs as a result of higher pressure in the blood vessels than outside the blood vessel. In Indonesia, many plants used as herbal medicine. Binahong (anredera cordifolia (tenore) steenis) contains flavonoids, terpenoids, essential oils, tannins. Soursop (annona muricata l.) leaf contains flavonoids, triterpenoids, saponins, polyphenols, tannins. The purpose of this study is to determine the effectiveness of binahong leaves extract, soursop leaves and combination of binahong and soursop leaves extract on hemostasis process in cuts of mice.Material and Methods: This research was conducted at the Phytochemicals Laboratory Faculty of Pharmacy and Entomology Laboratory Medical Hasanuddin University. This research is laboratory experimental with post test only with control group design. First stage by making binahong and soursoup leaves extract using maceration techniques. Male mice were adapted for seven days. Treatment on day eight by cutting the tail as much as 1 cm from the tip of the tail. Bleeding time is calculated after dipping tip of tail into the extract for 5 seconds until no blood dripping on gauze pads. Data were analyzed using kruskal wallis test followed by mann-whitney test.Results: Binahong leaves extract, soursop leaves extract and combination of binahong and soursop leaves extracts affected hemostasis on cuts of male mice (mus musculus).Conclusion: Combination binahong and soursop leaves extracts have the best effectiveness.